Three-Dimensionally Conformal Porous Microstructured Fabrics via Breath Figures: A Nature-Inspired Approach for Novel Surface Modification of Textiles - Jianliang Gong (Nature Portfolio, 2017)
Abstract Breath figures (BFs) are a kind of water droplet arrays that can be formed by condensing aqueous vapor onto a cold surface, such as dewy phenomenon on a spider web. This study developed a BF-inspired approach for direct introduction of desired materials onto the textile surfaces with three-dimensionally conformal porous microstructures by the evaporation of solution-coated fabric under high humidity environment, which brings a brand-new kind of modified textiles, three-dimensionally conformal porous microstructured fabrics (CPMFs). Such kind of CPMFs can possess customized multifunctional properties of introduced materials, and meanwhile maintain the inherent properties and unique texture features of fabrics. This nature-inspired BF approach is robust and versatile for customized preparation of CPMFs based on different fabrics with different common polymers. Moreover, it is also feasible for one-step functionalization of CPMFs by the incorporation of nanoparticles (such as titanium dioxide nanoparticles, TiO2 NPs) into the porous microstructures during the BF process. Comparing to the sample modified without porous microstructures, the resultant TiO2 NPs-incorporated CPMFs show an obviously enhanced performance on photocatalytic degradation of pollutants under the same ultraviolet irradiation conditions.